2000
DOI: 10.1002/1522-2683(20000601)21:11<2219::aid-elps2219>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Tracking pathology with proteomics: Identification ofin vivo degradation products of αB-crystallin

Abstract: Soemmerring's ring is one form of "after cataract" that can occur following cataract surgery. The ring structure is formed by adherence of the anterior lens capsule to the posterior lens capsule. Epithelial cells remaining after surgery differentiate into lens fiber cells but the resulting tissue mass does not remain transparent. The protein in normal lens and in Soemmerring's rings from four individuals was analyzed using two-dimensional (2-D) gel electrophoresis, matrix assisted laser desorption/ionization-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Elevated amounts of truncated αB 1-174 have been observed in cataracts from some human patients 11, in Soemmerring’s ring “after” cataract 36, and in an infant with persistent hyperplastic primary vitreous where cells invade the posterior lens 11. A major finding of the present investigation was that elevation of lenticular calcium by A23187 also produced αB 1-174 in cultured human lenses, and that the process could be reproduced in cultured monkey lenses.…”
Section: Discussionsupporting
confidence: 61%
“…Elevated amounts of truncated αB 1-174 have been observed in cataracts from some human patients 11, in Soemmerring’s ring “after” cataract 36, and in an infant with persistent hyperplastic primary vitreous where cells invade the posterior lens 11. A major finding of the present investigation was that elevation of lenticular calcium by A23187 also produced αB 1-174 in cultured human lenses, and that the process could be reproduced in cultured monkey lenses.…”
Section: Discussionsupporting
confidence: 61%
“…The first dimension isoelectric focusing was performed using a BioRad Protean IEF Cell with 7 cm 3-10NL immobilized pH gradient strips (Colvis et al, 2000). Frozen lens samples were homogenized on ice with 8 M urea containing 4% CHAPS and 100 mM DTT (rehydration buffer).…”
Section: D Gel Electrophoresismentioning
confidence: 99%
“…3c). ␣B 1-170 and ␣B 1-163 were also found in human lens fiber cells growing in lens capsules following cataract surgery (21). This suggested that calpains are also active in human lens.…”
Section: Table I Masses and Identities Of Truncated ␣-Crystallins Promentioning
confidence: 99%